PENGARUH PENDEKATAN REALISTIC MATHEMATIC EDUCATION TERHADAP HASIL BELAJAR SISWA PADA MATERI BILANGAN DI SMP - Ismi, Redya; Mirza, Ade; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe thesis entitled the influence of the Realistic Mathematics Education approach on student achievement in Pontianak MTs N 2 aimed to examine the influence of the Realistic Mathematics Education approach on student achievement at Pontianak MTs N 2. The method used in this study was a pre-experimental design  with the research design used was one group pretest-posttest design. The population in this study were students of class VII at MTs N 2 Pontianak. The sample of this study was the students of class VII K who were selected using the purposive sampling technique.The data collection technique used is a achievement test. The pretest and posttest data were analyzed using the Wilcoxon-test after fulfilling the normality test. Analysis of student achievement obtained by Asymp. Sig (2-tailed) from the Wilcoxon test is 0,000 < 0,05. Thus it can be concluded that there is a positive and significant effect of the Realistic Mathematic Education approach on student achievement. Keywords:    Realistic Mathematic Education (RME), Student Achievement, Numbers